Fisheries Resource Management of Lake Tempe Based on Co-Management in Wajo Regency, Southern Sulawesi - Agus Kurniawan B; MH Abbas; Asriani Asriani; Andi Dian Ahirta (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
One of the most important sectors in Wajo Regency, South Sulawesi is the fisheries sector. This sector contributes to regional income, food security, and job creation. Lake Tempe has several problems such as conflicts between fishermen, unrestricted access to new technology, inadequate management of fisheries resources, uncontrolled fishing, and traditional community-based fisheries management. Co-management is carried out to organize activities in fisheries management. For this reason, it is necessary to strengthen institutions in managing the use of fishery resources and developing networks between fishing communities. This research was conducted using a structured questionnaire to identify and integrate the co-management model in Lake Tempe. There are relevant findings regarding this research, some of which are: (1) Goals, (2) Targets, and (3) Strategies, namely infrastructure strategy, banking services, coordination between authorities, organizational structure, cooperation, formation of cooperatives, training programs, and utilizing local wisdom. Natural resource management is a form of adaptive management, co-management, and change governance. Stakeholder involvement in improving conservation management and taking socio-economic aspects of the characteristics of the Tempe Lake area is an important element in efforts to design and implement co-management in fisheries resource management.